Multicultural Political Communication (Case Study of Political Communication Bulan Bintang Party in North Sumatra Province) - Hasrat Efendi Samosir (The Islamic Education and Multiculturalism Foundation, 2023)
This research is intended to provide answers to the questions contained in this study, namely to describe the process of multicultural political communication Bulan Bintang Party carried out by the Regional Representative Council of the Bulan Bintang Party (DPW PBB) in North Sumatra. The results of this study, that there are forms of multicultural political communication in the DPW PBB North Sumatra that are interpersonal communication, namely silaturahim, visits between figures, door to door or direct selling. The Bulan Bintang party (PBB) in the North Sumatra, a special institution called KAPPU (Committee for Action to Win Elections) was also formed to bridge group communication between party leaders, administrators, members and the public, especially those who are very multicultural in order to obtain qualified and popular legislative candidates in society.